Ramuan jamu herbal pada pakan terhadap performa pertumbuhan ikan nila (Oreochromis sp) - Pramono, Taufik Budhi; Marnani, Sri; Junaidi, Teuku; Setyawan, Agung Cahyo; Nasikhah, Ais Lulu; Wulan, Triana Sri (Fishery Product Technology Study Program, Yudharta University, Pasuruan, 2023)
Immunity and growth were problems in main focus in fish farming bussiness. The use of herbal ingredients in feed can be a solution. The aim of this research was to determine the effect of adding herbal supplements to feed in increasing the growth of Tilapia. The method used was a field experiment bya selecting tilapia in pond (8x3 m2). Adding natural supplements to feed begins with making herbal concoctions, then supplementing them with 50 mL/Kg feed..Fish were given feed at 3%/body weight for 1 month. The absolute growth in lenght and weight were 7.09±1.38 cm and 136.05±27.48 g. The feed conversation ratio was around 1.28, the feed efficiency was around 77.7% and the survival rate reached 100%. Herbal concoctions can increase immunity and optimal growth. .